Asymmetric inheritance of cytoophidia in Schizosaccharomyces pombe. - Zhang, J; Hulme, L; Liu, J (2014)
A general view is that Schizosaccharomyces pombe undergoes symmetric cell division with two daughter cells inheriting equal shares of the content from the mother cell. Here we show that CTP synthase, a metabolic enzyme responsible for the de novo synthesis of the nucleotide CTP, can form filamentous cytoophidia in the cytoplasm and nucleus of S. pombe cells. Surprisingly, we observe that both cytoplasmic and nuclear cytoophidia are asymmetrically inherited during cell division. Our time-lapse studies suggest that cytoophidia are dynamic. Once the mother cell divides, the cytoplasmic and nuclear cytoophidia independently partition into one of the two daughter cells. Although the two daughter cells differ from one another morphologically, they possess similar chances of inheriting the cytoplasmic cytoophidium from the mother cell, suggesting that the partition of cytoophidium is a stochastic process. Our findings on asymmetric inheritance of cytoophidia in S. pombe offer an exciting opportunity to study the inheritance of metabolic enzymes in a well-studied model system.